فعالية استخدام طريقة PQ4R لتنمية مهارة القراءة لدى طلبة مدرسة كديري الثانوية الإسلامية الحكومية الأولى في الصف الحادي عشر - Munjiyat, Munjiyat; Fuadiyah, Rizka A’yuna (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2018)
Teacher creativity and innovation are extremely needed in teaching Arabic material which is difficult for millennial learners to be understood, especially the competence in reading classical Arabic texts and tending to be stuck up in the understanding of qawaid. Therefore, this study aims to determine the process of using the PQ4R method and measure its level of effectiveness in improving students' reading skills in Arabic subject of class XI MAN 1 Kota Kediri. The method applied in this research is quantitative approach with experimental research model. The researcher used documentation, tests, and interview to collect the data in MAN 1 Kota Kediri in class XI. The data analysis used t-test with paired sample t-test. The result shows that PQ4R method is effective in improving reading skills, with the calculation result of pre-test score in the experimental class 66.08 and the control class 65.08 with a difference of 1.00. The results of post-test of experimental class 86.52 and 63.04 control class with a difference of 23.48, so the experimental class using the PQ4R method is higher than the control class. The data analysis used is t-test with the calculation of sig (2-tiled), with the result of sig (2-tiled) = 0.00, because the result of sig (2-tiled) 0.00> 0.05. So it can be concluded that the PQ4R method provides an easier way to comprehend Arabic reading texts.